Praktik Pemasaran Digital di Hotel Jimbarwana Jembrana Bali - Rahmat Hidayat; I Made Darma Oka; Ni Gst Nym Suci Murni (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2026)
This study aims to analyze and formulate an ideal digital marketing innovation model to increase occupancy at the Jimbarwana Hotel in Jembrana Regency. Using quantitative and qualitative (explanatory) approaches, this study examines five types of digital marketing: website, social media, SEO, email marketing, and online advertising. The quantitative analysis shows that all types of digital marketing have a significant influence on digital marketing innovation. Specifically, website (0.221) and online advertising (0.218) have a very strong influence, followed by social media (0.207), email marketing (0.242), and SEO (0.236). Furthermore, digital marketing innovation is proven to have a very strong and significant influence on digital marketing effectiveness (0.779). The qualitative analysis strengthens these findings by identifying key strategies for each digital element. The website is seen as the "digital face" that must prioritize speed and easy navigation. The use of SEO and SEM is considered crucial for visibility, despite having to compete with OTAs. Social media such as Instagram and TikTok are effective for engagement, while email marketing is used for customer retention. Online advertising (Google Ads, Meta Ads) is considered essential for reach, but it needs to be managed efficiently. Overall, this study formulates a holistic digital marketing model that integrates various platforms to address hotel occupancy challenges.